RBV-Based Dynamic Capabilities as a Strategy for MSMEs in the Processed Food Sector in the Global Economy : (A Study of Local Processed Food Producers in Tulungagung, East Java) - Landreas Utama Lie; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The objective of this study is to develop a theoretical framework that can be used to identify the key resources and capabilities involved in the globalization process. This case study aims to examine how export-oriented small businesses in Indonesia achieve success at the international level. To obtain qualitative data, in-depth interviews were conducted with the Makmur Susanti Group, an MSME in Tulungagung, East Java. This study, based on the Resource-Based View (RBV), demonstrates how dynamic capabilities in production, networking, marketing, learning, legal, and synergistic areas contribute to the formation of competitive advantages that support business sustainability and continuity. The study indicates that success in internationalization requires a combination of capabilities that can meet market needs, rather than a single capability. This study contributes to the literature by offering a comprehensive framework of the internationalization process and providing practical insights for policymakers and practitioners aiming to enhance the competitiveness of SMEs. The research findings underscore the importance of capability development and government support in facilitating the global expansion of SMEs. Ultimately, this study provides a foundation for further investigation into the dynamic capabilities required for SMEs to thrive in international markets.